2017
DOI: 10.4172/2155-9570.1000635
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunohistochemical Features of Sebaceous Carcinoma: Focusing on the p53 Tumor Suppressor

Abstract: Purpose: Considerable focus has recently revealed the importance of p53 in sebaceous carcinoma (SC). This study investigates the utility of p53 as an immunohistochemistry (IHC) marker for differentiating benign and malignant sebaceous tissues and reports the clinical characteristics of patients diagnosed with SC at Mount Sinai Hospital (MSH). Methods:A retrospective chart analysis of 102 patients with SC was performed in addition to a histopathological examination of benign and malignant sebaceous tissues. Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The low incidence of 0.16/100,000 person-years for sebaceous carcinoma in the US, as well as the small size of many biopsy specimens, means that it is difficult for a single institution to accumulate large cohorts with excess tissue for molecular analysis. [9] However, several studies have identified mutations in tumor suppressor genes, including TP53 and RB1, and p16 expression has been implicated as a robust immunohistochemical marker for these tumors [10][11][12][13][14][15][16][17][18][19]. High-risk human papillomavirus (HPV), whose oncogenes encode well-characterized inhibitors of p53 and Rb, has been detected in up to 18% of OA sebaceous carcinomas without concurrent tumor suppressor mutations, and additional studies have demonstrated overexpression of miRNAs that influence the p53 suppressor complex [6,11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The low incidence of 0.16/100,000 person-years for sebaceous carcinoma in the US, as well as the small size of many biopsy specimens, means that it is difficult for a single institution to accumulate large cohorts with excess tissue for molecular analysis. [9] However, several studies have identified mutations in tumor suppressor genes, including TP53 and RB1, and p16 expression has been implicated as a robust immunohistochemical marker for these tumors [10][11][12][13][14][15][16][17][18][19]. High-risk human papillomavirus (HPV), whose oncogenes encode well-characterized inhibitors of p53 and Rb, has been detected in up to 18% of OA sebaceous carcinomas without concurrent tumor suppressor mutations, and additional studies have demonstrated overexpression of miRNAs that influence the p53 suppressor complex [6,11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%